"Is it safe?" – Doing ethnography on safety cover ups. Issue 1 (3rd November 2020) - Vickers, David Andrew
Abstract : Purpose: The purpose of this paper is to explore the ethicality, morality and partiality of at-home ethnography (AHE) through an account of organisational wrongdoing at a chemical plant. Design/methodology/approach: The paper utilises an AHE example from an 18-month period at a chemical plant. Following the account, the paper reflexively explores ethical, moral and partial issues. Findings: A well-crafted and reflexive, insider account of organisational wrongdoing enables the demonstration of the issues of ethics, morals and partiality faced by an ethnographer in the field. Whilst this is not an autoethnographic account, it is able to draw upon some contemporary thinking from autoethnography to inform reflexivity. Originality/value: The account provides unique insight into an organizational world, the inner workings of a chemical site, which is often inaccessible to others.